2011
DOI: 10.1177/1089253211415123
|View full text |Cite
|
Sign up to set email alerts
|

Transesophageal Echocardiography–Guided Aortic Thrombectomy in a Patient With a Mobile Thoracic Aortic Thrombus

Abstract: Thoracic aortic thrombi are a well-known cause of distal embolic phenomena. There is a paucity of case reports because of the rarity of this condition, and thus clear management guidelines are lacking. The authors present a case of a mobile thoracic aortic thrombus managed by a surgical approach. This report demonstrates how intraoperative transesophageal echocardiography (TEE) proved to be critical in guiding surgical management. The utility of TEE in the diagnosis and management of aortic thrombi is also dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…Endovascular therapies include stent placement over the AMT, catheter-directed thrombolysis and thrombus aspiration 17. Endovascular management is associated with a 5.7% failure or recurrence rate 1.…”
Section: Discussionmentioning
confidence: 99%
“…Endovascular therapies include stent placement over the AMT, catheter-directed thrombolysis and thrombus aspiration 17. Endovascular management is associated with a 5.7% failure or recurrence rate 1.…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports endorse the use of continued oral anticoagulation after either open surgical repair or TEVAR. 7,10,12,16,18,22,23,25,29,30,36 Some of these decisions may have been based on the desire to protect the distal vascular territory that was damaged by prior emboli and directly related to TEVAR placement. Thus, it is unclear whether the perceived success of surgical therapy is dependent on adjuvant medical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly encountered cardioembolic presentations include stroke [36], an acutely threatened limb or blue toe syndrome [7, 8], and abdominal ischaemic syndromes [3, 911], including renal or splenic infarcts and mesenteric ischaemia. However, a few authors have reported asymptomatic TAMT following thoracic CTA done for unrelated reasons, including to rule out pulmonary emboli or an acute traumatic aortic syndrome [12, 13].…”
Section: Discussionmentioning
confidence: 99%
“…In this instance, thrombosis is most commonly due to a prothrombotic state, whether hereditary or acquired [10]. In addition, an underlying proinflammatory state associated with inflammatory bowel disease or systemic autoimmune collagen vascular disease such as rheumatoid arthritis has been reported as the underlying cause of thrombosis by Elder et al [8] and Krishnamoorthy et al [11], respectively. Despite exhaustive investigation, no cause could be identified in a strikingly large number of cases [3, 6, 12], as in this case.…”
Section: Discussionmentioning
confidence: 99%